Roles of multiple-proton transfer pathways and proton-coupled electron transfer in the reactivity of the bis-Fe(IV) state of MauG - Ma, Zhongxin (Proc Natl Acad Sci U S A, 2015)
The high-valent state of the diheme enzyme MauG exhibits charge–resonance (CR) stabilization in which the major species is a bis-Fe(IV) state with one heme present as Fe(IV)=O and the other as Fe(IV) with axial heme ligands provided by His and Tyr side chains. In the absence of its substrate, the high-valent state is relatively stable and returns to the diferric state over several minutes. It is shown that this process occurs in two phases. The first phase is redistribution of the resonance species that support the CR. The second phase is the loss of CR and reduction to the diferric state. Thermodynamic analysis revealed that the rates of the two phases exhibited different temperature dependencies and activation energies of 8.9 and 19.6 kcal/mol. The two phases exhibited kinetic solvent isotope effects of 2.5 and 2.3. Proton inventory plots of each reaction phase exhibited extreme curvature that could not be fit to models for one- or multiple-proton transfers in the transition state. Each did fit well to a model for two alternative pathways for proton transfer, each involving multiple protons. In each case the experimentally determined fractionation factors were consistent with one of the pathways involving tunneling. The percent of the reaction that involved the tunneling pathway differed for the two reaction phases. Using the crystal structure of MauG it was possible to propose proton–transfer pathways consistent with the experimental data using water molecules and amino acid side chains in the distal pocket of the high-spin heme.